The road to crisis: State of Pakistan’s Research Output in Dementia - Ahmed, Tehniat Faraz; Ahmed, Affan (Journal of the Pakistan Medical Association, 2023)
Dear Madam, With an estimated 6.5 million people living with dementia in the South Asian region, these areas are at the forefront of tackling the growing epidemic. However, there is a scarcity of population-based studies particularly in lower-middle-income countries, which hampers accurate estimation of the economic burden posed by dementia (1). Pakistan, with the world’s third largest growing population is a model of these countries. Although the Global Action Plan for Public Health Response to Dementia highlights seven action areas, the Global Dementia Observatory (GDO) report has Pakistan underperforming in almost all areas. In comparison, her neighbors, India, China and Iran are significantly better. With no health information systems for dementia, and no support or care for people with dementia, Pakistan has failed to consider dementia as a public health priority (1). Reports show that Pakistan is drafting a national policy for dementia, yet no surveys on national prevalence and cost have been conducted (2). Apart from an ageing population, low literacy levels and high prevalence of heart diseases and diabetes, make the population highly susceptible to developing AD in the coming future. Furthermore, a challenge especially to LMICs is the stigma associated with dementia and the lack of awareness, not just in the general population, but also in the healthcare providers. Alzheimer’s Disease International reports that almost 2 in 3 healthcare practitioners worldwide consider dementia as part of normal ageing (3). Only if these beliefs are reformed can the disease be tackled efficiently. For a nation with no infrastructure to support patients with AD and where MRI is unaffordable to the majority and scarcely available PET scans are not used for the diagnosis of AD, the population would rely on the establishment of fluid biomarkers not only for diagnosing AD, but for its identification at a stage where it is possible to reduce the years lost to dependence. Unfortunately, our search on PubMed and Google Scholar revealed only one AD biomarker study conducted by the current authors on our population (4). Recently a constructive step was taken by lay and professional experts where a SWOT analysis was done of dementia research capacity in Pakistan. ---Continue